Retracted: Preconception Care through Religious Leaders in Bangladesh – A Novel Approach (Delta Medical College Journal, 2018)
The following retraction notice for this article appears in Vol.6(2) 2018 https://doi.org/10.3329/dmcj.v6i2.40608.On 18th March 2019 the Editorial Board of Delta Medical College Journal agreed to retract the Editorial 'Preconception Care through Religious Leaders in Bangladesh – A Novel Approach’ published in Delta Medical College Journal, Vol.6(2) pages 59-61 (DOI: https://doi.org/10.3329/dmcj.v6i2.38212) as the authors had already committed it for publication elsewhere. This error is regretted, and we apologise for any inconvenience.